HUBUNGAN FAKTOR INDIVIDU DAN FAKTOR PEKERJAAN DENGAN TINGKAT KELELAHAN KERJA DI DINAS A PT. X TAHUN 2022 - Handayani, Melizha; Demiyati, Cici (Jurnal Kesehatan Masyarakat, 2023)
Work fatigue is a condition where the ability of physical or mental performance is reduced and it can be impact on the occurrence of incidents. Based on the interview results at PT GMF AeroAsia Tbk, there are a number of personnel who work 12 hours a day which can trigger high work fatigue. The aim of this study was to determine the correlation between individual factors and work-related factors with work fatigue levels in Division A, PT. X. This study used a cross-sectional approach of quantitative observations. Total sample was 45 respondents with sampling method used is proportionate random sampling. Data was collected using a questionnaire and data analysis was performed using the chi square test. The results showed that the most personnel of Division A experienced a moderate level of fatigue. The statistical test results showed there is significant correlation between age (p= 0,034) and duration of work (p=0,038) with work fatigue levels. While the variables of working period (p=0,115), sleep duration (p=0,227), and work shift (p=0,150) did not have a significant correlation with fatigue levels on personnel of Division A, PT. X in 2022. Individual factor correlated with work fatigue is age, while the work-related factor is the duration of work. Therefore, companies are advised to limit working hours in one shift to less than 12 hours and the total overtime is a maximum of 13 hours a week.